2017
DOI: 10.1016/j.chom.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Shigella sonnei Encodes a Functional T6SS Used for Interbacterial Competition and Niche Occupancy

Abstract: Shigella is a leading cause of dysentery worldwide, with the majority of infections caused by two subgroups, S. flexneri and S. sonnei. Although S. flexneri has been highly prevalent in low-income countries, global development has brought an increase in S. sonnei at the expense of S. flexneri. However, the mechanisms behind this shift are not understood. Here we report that S. sonnei, but not S. flexneri, encodes a type VI secretion system (T6SS) that provides a competitive advantage in the gut. S. sonnei comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
129
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 43 publications
6
129
0
1
Order By: Relevance
“…Additional work demonstrated that T6S contributes to the fitness of Bacteroides fragilis in competition with other bacteria in vitro and in gnotobiotic mice (Chatzidaki-Livanis et al, 2016; Hecht et al, 2016; Russell et al, 2014b; Wexler et al, 2016). These and other data show that the mammalian GI tract is physically conducive to T6SS-dependent interbacterial antagonism, suggesting a potential impact of this pathway on the composition of the human gut microbiome (Anderson et al, 2017; Sana et al, 2016). Here, we sought to define the distribution of the Bacteroidales T6SS and to explore its function in the human gut microbiome through the analysis of several publicly available metagenomic datasets.…”
Section: Introductionsupporting
confidence: 57%
“…Additional work demonstrated that T6S contributes to the fitness of Bacteroides fragilis in competition with other bacteria in vitro and in gnotobiotic mice (Chatzidaki-Livanis et al, 2016; Hecht et al, 2016; Russell et al, 2014b; Wexler et al, 2016). These and other data show that the mammalian GI tract is physically conducive to T6SS-dependent interbacterial antagonism, suggesting a potential impact of this pathway on the composition of the human gut microbiome (Anderson et al, 2017; Sana et al, 2016). Here, we sought to define the distribution of the Bacteroidales T6SS and to explore its function in the human gut microbiome through the analysis of several publicly available metagenomic datasets.…”
Section: Introductionsupporting
confidence: 57%
“…Through cycles of extension and contraction, this pathway delivers effector proteins from the cytoplasm of a donor bacterium directly into the periplasm or cytoplasm of a recipient bacterium (3,4). Used by both pathogenic and commensal bacteria of eukaryotes, the T6SS mediates a complex interplay of bacterial cell-cell interactions between beneficial and disease-causing bacteria (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The Salmonella Pathogenicity Island Six encodes a T6SS cluster that contributes to the colonisation of mice and chickens. The T6SS of pathogenic Shigella sonnei is also required to colonise the mouse gut (Anderson, Vonaesch, Saffarian, Marteyn, & Sansonetti, 2017). However, no killing of other Gramnegative bacteria was observed (e.g., Enterobacter cloacae, Escherichia coli, or commensals such as Prevotella copri, Parabacteroides distasonis, and Bifidobacterium longum; Sana et al, 2016).…”
Section: The T6ss Arms Race In the Control Of Gut Microbiota/ Pathomentioning
confidence: 99%